PHYSICAL-CHEMICAL AND SENSORY CHARACTERIZATION OF JELLIES FROM INDUSTRIALIZED MURUCI PULP (BYRSONIMACRASSIFÓLIA) (REMUNOM, 2025)
Muruci is a fruit widely distributed throughout the Amazon region, and is also found in areas of theNortheast and Central-West of Brazil. It can be consumed both in natura and processed, used in theproduction of juice, creams, jellies, among others. This research aimed to characterize the physical-chemical and sensory parameters of industrialized muruci pulp jellies from three differentmanufacturers (A, B and C). The results obtained demonstrated that the jellies meet the qualitystandards, with variations in TSS and acidity. The sensory analysis showed high acceptability rates,above 70%, with Jelly A standing out in color and flavor, and Jelly C in texture and aroma. Regardingthe gender of the participants, there was good acceptance, especially of Jelly C, followed by A. Theabsence of significant statistical differences between the groups indicates the market potential of muruci jellies for both genders. The interest in consumption, together with its nutritional and sensoryqualities, positions muruci as a promising raw material for the food industry. The study emphasizesthe relevance of products derived from the industrialized pulp of native fruits, such as muruci, helpingto enhance national products and presenting new alternatives for the consumer market.